Kepastian Hukum dalam Perjanjian Sebagai Fondasi Kepercayaan Publik Terhadap Lembaga Penegak Hukum di Indonesia - Indriati Indriati (Dialog Legal: Jurnal Syariah, Jurisprudensi dan Tata Negara, 2025)
Legal certainty in contracts constitutes a fundamental foundation for safeguarding the rights and obligations of the parties and for strengthening public trust in law enforcement institutions. However, in practice, contract litigation often encounters various obstacles, including the complexity of evidentiary procedures, prolonged case resolution, and difficulties in enforcing court judgments. These conditions influence public perceptions of the integrity and institutional capacity of the judiciary in delivering justice. This study aims to analyze the relationship between legal certainty in contracts and the level of public trust in law enforcement institutions, particularly through public experiences in litigation processes involving breaches of contract. This research employs a qualitative approach using a literature review method that examines relevant academic literature, statutory regulations, and court decisions related to contract law and the effectiveness of the judicial system. The findings indicate that the complexity of evidentiary procedures, extended duration of case resolution, and challenges in enforcing court decisions are key factors shaping public perceptions of judicial effectiveness. An analysis of Decision Number 05/PDT/2020/PT SMR demonstrates that the quality of judicial decisions and the effectiveness of their enforcement are closely linked to the level of public trust in legal authorities. Therefore, improving the quality of judicial reasoning, simplifying procedural mechanisms, and strengthening enforcement processes are essential steps to reinforce legal certainty in contractual relations while enhancing public confidence in Indonesia’s legal system.